MODEL KONSELING KELOMPOK DENGAN TEKNIK BERMAIN PERAN UNTUK MENGEMBANGKAN KETERAMPILAN SOSIAL ANAK DENGAN HIGH FUNCTIONING AUTISM DISEKOLAH DASAR INKLUSIF - Sensus, Agus Irawan (2014)
Agus Irawan Sensus, 2014. Group Counseling Model with Role-Playing Technique to Develop the Social Skills of Children with High Functioning Autism in Inclusive Primary Schools. Dissertation. Supervised by: Prof. H. Furqon, Ph.D. (Promoter); Prof. Dr. H. A. Juntika Nurihsan, M.Pd. (Co-promoter); and Dr. H. Zaenal Alimin, M.Ed. (Member). Guidance and Counseling Study Program, School of Postgraduate Studies, Indonesia University of Education, Bandung. The difficulty of children with high functioning autism (HFA) in interacting with their environment will hinder their other activities. To solve this problem, an environmental intervention based on empirical and conceptual analysis is needed. The research is aimed to formulate an effective group counseling model with role playing to develop the social skills of children with HFA in inclusive primary schools in Bandung City. Research method employed research and development with exploratory mixed-method design. The subjects of this qualitative research were teachers, principals, and parents of children with HFA, and four children with HFA. The group counseling model with role playing technique is effective to develop the social skills of children with HFA in inclusive primary schools. The analysis of the effectiveness of this group counseling model with role-playing technique used A-B-A design. The conclusion of this research has limitations to be generalized in a broader research context and setting. It is recommended that PPPPTK TK and PLB (Center for Development and Empowerment of Teachers and Education Personnel of Kindergarten and Special Needs Education) can use the structure of education and training program for inclusive primary school teachers. Inclusive schools and teachers are suggested to implement an effective group counseling model with role-playing technique by referencing the guidance resulted in this research. In addition, future researchers can research other aspects related to group counseling with other research methods and approaches and data analysis techniques.